2018
DOI: 10.1088/1748-9326/aabcd8
|View full text |Cite
|
Sign up to set email alerts
|

Differential ecophysiological responses and resilience to heat wave events in four co-occurring temperate tree species

Abstract: Extreme summer heat waves are known to induce foliar and stem mortality in temperate forest ecosystems, yet our mechanistic knowledge of physiological thresholds for damage is lacking. Current spatiotemporal simulations of forest growth responses to climate change fail to explain the variability between co-occurring tree species to climate extremes, indicating a need for new model frameworks that include mechanistic understanding of trait-specific responses. In this context, using manipulative heat wave (hw) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…These results suggest impairment of energy transfer and production at high temperatures, particularly in EB since that species was most negatively affected by the heatwave. Guha et al, () identified similar relationships between heatwave tissue damage, reductions in A sat , and inhibition of PSII among four northern temperate tree species. We also found that the decline in PSII efficiency ( F v ʹ/ F m ʹ) was smallest in EC and largest in EB, indicating that EB was dissipating more excited energy to non‐photochemical quenching or possibly photorespiration than EC.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These results suggest impairment of energy transfer and production at high temperatures, particularly in EB since that species was most negatively affected by the heatwave. Guha et al, () identified similar relationships between heatwave tissue damage, reductions in A sat , and inhibition of PSII among four northern temperate tree species. We also found that the decline in PSII efficiency ( F v ʹ/ F m ʹ) was smallest in EC and largest in EB, indicating that EB was dissipating more excited energy to non‐photochemical quenching or possibly photorespiration than EC.…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest impairment of energy transfer and production at high temperatures, particularly in EB since that species was most negatively affected by the heatwave. Guha et al, (2018) However, short-term heat exposure is more likely to inhibit Rubisco activase and cause temporary deactivation of Rubisco than substantially reduce Calvin cycle enzyme concentrations (Haldimann & Feller, 2004;Hozain et al, 2010;Salvucci & Crafts-Brandner, 2004).…”
Section: Physiological and Biochemical Factors Associated With Specmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent small decline of chlorophyll fluorescence parameters in the heat treatment, measured 1 day after the last heat wave had ended, may either reflect a relative mild impairment of the photosynthetic apparatus, or indicate a fast recovery of chlorophyll fluorescence parameters 1 day after the acute stress. Fast recovery responses of photosynthetic parameters after acute heat waves (when water was not limiting) were observed in herbaceous plants, as well as in some tree species and typically relate to temperatures <45 • C (Hüve et al, 2011;Ameye et al, 2012;Guha et al, 2018). However, complete recovery of the few surviving seedlings in the heat-drought treatment seemed to be impaired.…”
Section: Photosynthetic Inhibition and Recovery From Acute Heat Stressmentioning
confidence: 99%
“…Furthermore, an increase in heat also negatively influenced the EVIavg, and HW and SU mainly had a negative impact on vegetation health for different elevations and vegetation types. There is evidence that extreme heat waves in summer can induce foliar and stem mortality in temperate forests [59,60]. However, the degree of response and impact can differ by species and region, and this study demonstrated the negative influence of increasing heat on Jeju's vegetation.…”
Section: Discussionmentioning
confidence: 60%